A Family of RuII Photosensitizers with High Singlet Oxygen Quantum Yield: Synthesis, Characterization, and Evaluation1. Issue 26 (16th July 2013) - Pefkianakis, Eleftherios K.; Christodouleas, Dionysios; Giokas, Dimosthenis L.; Papadopoulos, Kyriakos; Vougioukalakis, Georgios C.
Abstract: A series of Ru II ‐based photosensitizers were synthesized and extensively characterized. The ligand utilized to coordinate ruthenium was a pyridine–quinoline hybrid bearing an anthracene moiety, and it was combined with commercially available 2, 2′‐bipyridine (bpy) for the heteroleptic complexes. The produced bichromophoric complexes show very strong and wide UV/Vis absorption bands. The ability of these complexes to act as triplet photosensitizers in the production of singlet oxygen was thoroughly studied by utilizing the photooxidation of 1, 3‐diphenylisobenzofuran as the test reaction. The most efficient photosensitizer in this new family of Ru II complexes affords singlet oxygen quantum yields and production‐rate efficiencies up to two times higher than those of the benchmark [Ru(bpy)3 ] 2+ parent complex. Abstract : A series of ruthenium complexes bearing a pyridine–quinoline hybrid ligand were synthesized and extensively characterized. The 1 O2 generation quantum yield of these complexes is enhanced in comparison with that of the benchmark parent complex [Ru(bpy)3 ]Cl2 (bpy = 2, 2′‐bipyridine), and the most efficient complex outperforms the parent complex by up to two times.